2004
DOI: 10.1016/j.febslet.2004.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chloride intracellular channel proteins in spermatozoa

Abstract: We have identified for the first time the presence of chloride intracellular channel (CLIC) proteins in bovine epididymal spermatozoa. CLIC1 was discovered during microsequencing of proteins that co-purified with protein phosphatase 1, PP1c2, in sperm extracts. In addition to CLIC1, Western blot showed that two additional CLIC family members, CLIC4 and CLIC5, are also present in spermatozoa. CLIC fusion proteins, GST-CLIC1, GST-CLIC4 and GST-CLIC5, were all able to bind to PP1c2 in sperm extracts during pull-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This is consistent with an earlier report that Clic4 transcripts increase rapidly in 3T3L1 cells induced to differentiate into adipocytes in vitro [41]. Previous studies had also identified the presence of CLIC4 along with CLIC1 and CLIC5 in bovine spermatozoa [42]. Our probing in mouse testes indicates a predominant expression of CLIC4 in spermatogonia implying an early role for the protein in spermatogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with an earlier report that Clic4 transcripts increase rapidly in 3T3L1 cells induced to differentiate into adipocytes in vitro [41]. Previous studies had also identified the presence of CLIC4 along with CLIC1 and CLIC5 in bovine spermatozoa [42]. Our probing in mouse testes indicates a predominant expression of CLIC4 in spermatogonia implying an early role for the protein in spermatogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…The ClC proteins are present in bovine epididymal spermatozoa12 and can bind PP1γ2, a key enzyme involved in regulating sperm maturation and motility. The ClC-3 channels are expressed in healthy human spermatozoa and are involved in sperm volume regulation 6.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of transmembrane Cl − transport results in failure of sperm penetration and migration through surrogate cervical mucus 11. ClC channels have been found in the bovine testicular and epididymal spermatozoa,12 and recently in healthy human spermatozoa 6. The ClC proteins can bind to protein phosphatase 1 (PP1γ2), which is required for regulating sperm motility 13.…”
Section: Introductionmentioning
confidence: 99%
“…The sperm motility is a key factor to determine semen quality and its fertilizing capacity (104)(105)(106), which is widely controlled by a variety of factors (107)(108)(109). The phospholipid composition and cholesterol to phospholipid ratio are predominant factors required for the sperm maturation in the epididymis (110).…”
Section: Fertilizationmentioning
confidence: 99%